Dendritic Spines and Development: Towards a Unifying Model of Spinogenesis—A Present Day Review of Cajal's Histological Slides and Drawings - Pablo García-López; Virginia García-Marín; Miguel Freire (Neural Plasticity)
Dendritic spines receive the majority of excitatory connections in the central nervous system, and, thus, they are key structures in the regulation of neural activity. Hence, the cellular and molecular mechanisms underlying their generation and plasticity, both during development and in adulthood, are a matter of fundamental and practical interest. Indeed, a better understanding of these mechanisms should provide clues to the development of novel clinical therapies. Here, we present original results obtained from high-quality images of Cajal's histological preparations, stored at the Cajal Museum (Instituto Cajal, CSIC), obtained using extended focus imaging, three-dimensional reconstruction, and rendering. Based on the data available in the literature regarding the formation of dendritic spines during development and our results, we propose a unifying model for dendritic spine development.